Bridging the Gap: Linking and Matching Educational, Spirituality, Sciences, School Principal Leadership, Link & Match Concept between the Educational and Bussiness and Professional Realms for Optimal Education Quality and Sports Achievement - Tursinah Anggendari; Sarah Fitriyani (International Journal of Economics and Management Research, 2022)
This qualitative research aims to explore the integration of educational, spiritual, and scientific principles with business dynamics to optimize educational quality and sports achievement. The study employs a Link & Match concept, emphasizing the correlation between educational leadership and business realms. Through purposive sampling, school principals and professionals from various fields will be selected. Data analysis involves thematic analysis to identify patterns and connections between educational leadership, business practices, and holistic development. The findings are expected to highlight effective strategies for synergizing educational, spiritual, and scientific aspects with business principles, ultimately enhancing education quality and fostering sports excellence in educational institutions.